Estimasi Lokasi Gangguan Hubung Singkat pada Saluran Transmisi Tenaga Listrik - Syahputra, Romadoni (Semesta Teknika, 2014)
In this paper, a method for short circuit fault location estimation which uses data from both ends of overhead transmission line and which does not require the data to be synchronized is described. The method fully utilizes the advantages of digital technology and numerical relaying which are available today and can easily be applied for off-line analysis. The described scheme does not require real-time communications, only off-line post-fault analysis. The method allows for accurate estimation of fault location irrespective of fault types, fault resistance, load currents, and source impedances. The simulation for single line to ground fault and symmetrical three phase fault with the variation of fault resistance of 0 ohm, 10 ohms, 30 ohms, 50 ohms, 70 ohms, and 100 ohms, respectively. The simulation has been done by using Matlab software. The simulation results of estimation error are 0.296% for single line to ground fault and 0.112% for symmetrical three phase fault, respectively. The results have shown that the method can accurately estimate the location of short circuit fault on power transmission lines.Â